Hadith-Based Communication Ethics for Responding to Hate Speech on TikTok - Azzahra, Mumtazah; Kusnadi, Kusnadi; Nurchalidin, Nurchalidin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
The growing prevalence of hate speech on TikTok indicates a serious disruption in digital communication ethics and may generate broader social consequences. This study analyzes forms of hate speech on TikTok and examines Prophetic hadiths related to communication ethics through the ma‘anil al-hadith approach. It also evaluates the relevance of these hadiths for responding to hate speech practices in contemporary social media, particularly TikTok. This study employs a qualitative library research method. Primary data are drawn from Sahih al-Bukhari No. 6476, Sunan al-Tirmidhi No. 1977, and a hadith encyclopedia database used to trace related narrations, while secondary data consist of books, scholarly articles, and other relevant literature. The findings suggest that hate speech on TikTok frequently appears as attacks on religious, ethnic, racial, and intergroup identities and may contribute to social conflict. The hadiths examined in this study emphasize the obligation to guard one’s speech, the ethical importance of tabayyun (verification of information), and the prohibition of communication that harms others. The study concludes that Prophetic hadiths on communication ethics remain contextually relevant for addressing hate speech on social media and may serve as a normative basis for cultivating digital communication grounded in moral responsibility and social welfare.